Excess mortality due to COVID-19 in Thailand between the pandemic and post-pandemic periods - Atthasit Dul-amnuay; Udomlack Peansukwech; Chattarikorn Hanapun; Amod Sharma (Scientific Reports)
Abstract The coronavirus disease 2019 (COVID-19) pandemic had a significant effect on mortality rates worldwide, with Thailand being no exception. Gaining insights into the impact of pandemic-related mortality is essential for assessing its broader consequences on public health. This study aimed to analyze excess deaths during the pandemic (January 1, 2020-September 30, 2022) and post-pandemic period (October 2022-December 2023) at regional and national levels in Thailand. Expected deaths were estimated using a negative-binomial model, utilizing 2015–2019 data to project deaths for 2020–2021, with adjustments for seasonality. We found that Thailand experienced 76,756 excess deaths during the COVID-19 pandemic, with a p-score of 5.24%, and 36,126 excess deaths with a p-score of 5.26% in the post-pandemic period. After the pandemic, excess deaths in some provinces were elevated but did not reach statistical significance. Pneumonia was the major contributor to the deaths. In conclusion, Thailand experienced excess mortality during both the pandemic and post-pandemic periods. The study has identified regional areas with excess deaths, and further investigation into these findings could support public health improvements and strengthen preparedness for future health crises.